Diachronic analysis application for the detection of soccer performance standards: a case study - Maneiro, R.; Amatria, M.; Anguera, M. T. (International Journal of Computer Science in Sport, 2020)
The purpose of this study is to analyse the interactions established by Gerard Piqué, one of the world's top defenders, within the general context of the team. The type of interactions (prospective and retrospective) that the player establishes with his team mates and opponents; the parts of the pitch where his actions are set in motion and later finished; his preferred skill or technical moves and finally his influence on set pieces are taken into account. His output throughout the 2012 UEFA Euro, where he played 100% of the game. The instrument of observation proposed by Maneiro & Amatria (2018) has been used. Polar coordinate analysis, a powerful tecnique capable of reducing the amount of data without compromising its analytical capacity, was used. The results showed significant interactions with players from the same and different lines thanks to technical actions of control, pass and carrying of ball. The analysis of the player's interactions within the general context of the team will provide other teams with tactical alternatives and allow themto organise special training programmes.